Crystallization and stability of different protein crystal modifications: A case study of lysozymeth. Issue 2 (7th January 2015) - Yu, Xiaoxi; Ulrich, Joachim; Wang, Jingkang
<x xml:space="preserve">Abstract</x> The phase diagram and phase transition of tetragonal and needle shaped lysozyme crystals under different pH values (4.5, 8.0, 9.0) were investigated. Tetragonal crystals can crystallize in the basic buffer at low temperature as well as in acid solutions, and will transfer to a needle modification when temperature and pH increases. In acid solutions, the needle shaped crystals will dissolve and tetragonal crystals will crystallize and remain in the solution. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>